2006
DOI: 10.1016/j.ejcts.2006.07.022
|View full text |Cite
|
Sign up to set email alerts
|

The role of leukocyte depleting filters in heart transplantation: early outcomes in prospective, randomized clinical trial

Abstract: The use of leukocyte depleting filters in heart transplantation is an effective, easy and safe method of myocardial protection, reducing significant myocardial reperfusion injury and improving posttransplant graft functional recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 19 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…There are examples in the literature of centers (UCLA, Albert‐Ludwigs‐University Freiburg) that have implemented different controlled reperfusion strategies in a standardized manner before aortic cross‐clamp release that are of interest to further investigate 22‐24 . In the report from the ISHLT consensus on PGF, Johns Hopkins University states that they drop FI O2 before the release of cross‐clamp which is not further explained but interesting 6 .…”
Section: Discussionmentioning
confidence: 99%
“…There are examples in the literature of centers (UCLA, Albert‐Ludwigs‐University Freiburg) that have implemented different controlled reperfusion strategies in a standardized manner before aortic cross‐clamp release that are of interest to further investigate 22‐24 . In the report from the ISHLT consensus on PGF, Johns Hopkins University states that they drop FI O2 before the release of cross‐clamp which is not further explained but interesting 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Continuous leukocyte filtration with arterial line filters incorporated into the circuit has shown mixed results in terms of attenuation of inflammation, oxidative stress, and organ dysfunction during and after CPB. It has also been reported that placing the leukocyte filter in venous line, while still efficiently filtering the leukocytes, may cause lower leukocyte damage and thus, better attenuate inflammation (160)(161)(162)(163)(164).…”
Section: Leukocyte Filtrationmentioning
confidence: 99%